Exploring Aplikasi Gojek dalam Mencapai Laba Organisasi - Hertati , Lesi; Yuliansyah, Yuliansyah (Penerbit Goodwood, 2024)
Purpose: This study aims to determine e-commerce and organizational performance in terms of organizational profits. As a form of e-commerce, e-commerce has become an integral part of modern business strategies. Organizational performance, which includes operational efficiency and goal achievement, is a key factor in achieving business success. Research methodology: The research method used in this study uses primary data from a questionnaire as a data collection instrument. The research sample was randomly selected from 43 Gojak users at Indo Global Mandiri University. The data used was an exploratory statistical method that measured the relationship between variables. Results: The results indicate that e-commerce and organizational performance contribute to increasing organizational profits. The use of technology can improve customer accessibility, operational efficiency, and an organization's ability to reach global markets. Organizational performance also plays an important role in determining profit levels. Organizations that perform well tend to achieve higher profits by providing a better understanding of the impact of e-commerce. Limitations: The importance of organizational performance in achieving profit goals and managerial roles can help organizations optimize strategies to improve their overall organizational performance and achieve better profits. Contribution: Follow-up studies could explore other aspects of e-commerce and organizational performance as well as consider additional variables to deepen the understanding of this relationship.